Comparative Evaluation of an Automated Repetitive-Sequence-Based PCR Instrument versus Pulsed-Field Gel Electrophoresis in the Setting of a Serratia marcescens Nosocomial Infection Outbreak - Ligozzi, Marco (American Society for Microbiology (ASM), 2010)
A semiautomated, repetitive-sequence-based PCR (rep-PCR) instrument (DiversiLab system) was evaluated in comparison with pulsed-field gel electrophoresis (PFGE) to investigate an outbreak of Serratia marcescens infections in a neonatal intensive care unit (NICU). A selection of 36 epidemiologically related and 8 epidemiologically unrelated isolates was analyzed. Among the epidemiologically related isolates, PFGE identified five genetically unrelated patterns. Thirty-two isolates from patients and wet nurses showed the same PFGE profile (pattern A). Genetically unrelated PFGE patterns were found in one patient (pattern B), in two wet nurses (patterns C and D), and in an environmental isolate from the NICU (pattern G). Rep-PCR identified seven different patterns, three of which included the 32 isolates of PFGE type A. One or two band differences in isolates of these three types allowed isolates to be categorized as similar and included in a unique cluster. Isolates of different PFGE types were also of unrelated rep-PCR types. All of the epidemiologically unrelated isolates were of different PFGE and rep-PCR types. The level of discrimination exhibited by rep-PCR with the DiversiLab system allowed us to conclude that this method was able to identify genetic similarity in a spatio-temporal cluster of S. marcescens isolates.